IMPLEMENTASI KEAMANAN SERVER PADA JARINGAN WIRELESS MENGGUNAKAN METODE INTRUSION DETECTION AND PREVENTION SYSTEM (IDPS) (STUDI KASUS : TECHNO’S STUDIO) - Muhammad Sadam Husain; LM Fid Aksara; Natalis Ransi (Informatics Engineering Department of Halu Oleo University, 2018)
The use of computer networks uses the current wireless media that provides significant information that allows others to access the connection because they do not use cables.Techno's Studio is a company engaged in technology and is a company that uses wireless technology as one of the important components in the activities of everyday employees. Therefore, server security issues on wireless networks become very important, because without any security support can lead to system failure and can be a gap in the occurrence of hacking.The IDPS method (Intrusion Detection & Prevention System) is used as an attack detection and prevention system by blocking Internet Protocol (IP) attackers. The results obtained from this research is the use of Snort and IPTables as a server security system on the wireless network successfully overcome the type of attack on ICMP ports, FTP, SSH, TELNET, and HTTP using various tools of attackers such as angry IP scanner, FileZilla, Putty, Mozilla Firefox, and Zenmap.Keywords— Server, Wireless, Intrusion Detection & Prevention System (IDPS), Snort, IPTables DOI: 10.5281/zenodo.1407864